Developing biases - van de Vijver, Ruben; Baer-Henney, Dinah (Frontiers in Psychology, 2014)
German nouns may alternate from singular to plural in two different ways. Some singular forms that end in a voiceless obstruent have a plural in which this obstruent is voiced. Another alternation concerns the vowel. Some singular forms with a back vowel have a plural form in which this back vowel is front. For each noun it has to be established individually whether it alternates or not. The voicing alternation is phonetically grounded, but the vowel alternation is not. Knowledge about such alternations involves two things. First, it involves knowledge of which words alternate and which words do not and second, it involves the ability to extend the alternations to novel words. We studied the knowledge of which words alternate and the proportion to which they alternate in two corpus studies. We studied the knowledge of speakers concerning which words alternate and what generalizations can be based upon these words by means of a production study. The production study involved words and nonces. We asked twenty 5 year-olds, twenty 7 year-olds and tenth adults to produce the plural for a given singular word and a plural for a given singular nonce. In the corpus study we found that both alternations occur with the same frequency. In the production of alternations in words we found that participants in all age groups make few mistakes. With respect to the production of alternations in nonce words, we found that the proportion of voicing alternations decreases with age, while the proportion of vowel alternations increases. We explain this change in the ability to generalize the alternations to nonces on the basis of the confidence speakers can have in a generalization. Young children have a small lexicon and they can form relatively unreliable generalizations on lexical distributions, but they can have more confidence in their knowledge of phonetics. Adults have a large lexicon and can therefore confidently form based on their lexicon.